THE INFLUENCE OF TRANSFORMATIONAL RANSFORMATIONAL LEADERSHIP CHARACTERISTICS ON SUCCESSION PLANNING PROGRAMS IN THE MALAYSIAN PUBLIC SECTOR (UUM Journal of Legal Studies, 2020)
Grooming successful leaders is more important now than ever for the public sector. Thus, to groom potential future leaders, the organization not only needs a succession planning program, but also commitment from the leaders. This paper analyzes the influence of leadership style characteristics on preparing future leaders through succession planning programs in Malaysia’s public sector. Four dimensions of transformational leadership styles were used which included idealized influence, inspirational motivation, individualized consideration, and intellectual stimulation. This study employed the Multifactor Leadership Questionnaire and the effective Succession Planning and Management Questionnaire which were administered to 394 public servants from Malaysia’s public sector. Data was analyzed using multiple regression analysis. The results of the multiple regression analysis demonstrated that individualized influence was the main predictor of succession planning programs. Therefore, it is crucial for leaders to continue observing and modifying their leadership style(s) and behavior to be effective leaders.